Medidas de proteção e controle de inundações urbanas na bacia do rio Mamanguape/PB - Barbosa, Francisco de Assis dos Reis (2006)
The urban floods are constituted one of the most important impacts on the society. Those impacts could happen due to the urbanization or to the natural flood of the riverside area. In the current context, several prevention and protection measures against urban floods are adopted, in general, measures of corrective character. The measures can be structural (when they modify the fluvial system and reduce risks of flood damages) and non-structural (a better coexistence of the population with the floods). This project has as main aim the elaboration of a plan of measures that contemplates the prevention aspects against the occupation of the spaces with flood risks, through structural and non-structural measures, associated or not, for the municipal districts located within Mamanguape river basin in Paraíba State, prone to floods since almost all of them occupy the flood plains of the main water courses. Several problems could be associated with the occurrence of those events: inadequate occupation of the river beds; lack of resources for dwelling and waste water system; lack of planning for the occupation of the urban space; and lack of systems for catastrophe alert and for evacuation of the flooded areas. Therefore, it is presented practical and efficient solutions for the best use of the risk areas, which would lead to a better life quality for the urban areas. The effective participation of the public government and the responsible department for the environmental and urban administration in the implementation of a politics of environmental education and elaboration of a management plan that prioritizes the flood control in the urban areas is indispensable